2023
DOI: 10.1055/a-2022-1905
|View full text |Cite
|
Sign up to set email alerts
|

Palladium-Catalyzed Unimolecular Fragment Coupling of N-Allylamides Bearing a Tethered Nucleophile with the Translocation of an Amide Group

Abstract: The palladium-catalyzed reaction of N-allylamides bearing a tethered nucleophile results in the extrusion of an amide moiety in the form of an isocyanate with its subsequent capture by the pendant nucleophile. This reaction involves the net catalytic transposition of an amide group.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…Our group recently reported on the palladium or nickel-catalyzed UFC of amides that proceed via the elimination of isocyanate from an allylic amide . In this Letter, we found that the reaction of allyl amides with a nickel catalyst produces a cationic π-allyl nickel species that contains the corresponding amide anion.…”
mentioning
confidence: 83%
“…Our group recently reported on the palladium or nickel-catalyzed UFC of amides that proceed via the elimination of isocyanate from an allylic amide . In this Letter, we found that the reaction of allyl amides with a nickel catalyst produces a cationic π-allyl nickel species that contains the corresponding amide anion.…”
mentioning
confidence: 83%
“…The overall process can be viewed as a catalytic transposition of an amide group from the middle to the terminal of the molecule (Scheme 23). 130 ■ ELIMINATION OF N 2 FROM 1,2-DIAZENES AND THEIR DERIVATIVES 1,2-Diazenes represent a class of nitrogen-bridged compounds and could be attractive substrates for UFC with the elimination of molecular nitrogen (N 2 ). Indeed, it is well-known that 1,2diazenes can eliminate N 2 by heating at high temperatures or by UV irradiation, which leaves behind carbon-centered radicals that can combine to form C−C bonds, particularly in the case of cyclic 1,2-diazenes (Scheme 24A).…”
Section: ■ Elimination Of Rnco From Amidesmentioning
confidence: 99%
“…The overall process can be viewed as a catalytic transposition of an amide group from the middle to the terminal of the molecule ( Scheme 23 ). 130 …”
Section: Elimination Of Rnco From Amidesmentioning
confidence: 99%
“…Our group recently reported on the nickel-catalyzed transformations of amides via the cleavage of the C­(acyl)–N bond . Building upon these studies, we hypothesized that amides bearing an alkynyl group (i.e., 1 ) would undergo cyclization if alkyne-directed oxidative addition of the C­(acyl)–N bond of amides and subsequent alkyne insertion were to occur (Scheme a).…”
mentioning
confidence: 99%